Rhodeus caspius, a new bitterling from Iran (Teleostei: Cypriniformes: Acheilognathidae) - Esmaeili, Hamid Reza; Sayyadzadeh, Golnaz; Japoshvili, Bella; Eagderi, Soheil; Abbasi, Keivan; Mousavi-Sabet, Hamed (Zootaxa, 2020)
A new bitterling from the Rhodeus amarus group is described based on morphological and molecular data. Rhodeus caspius sp. nov. from the Caspian Sea, Urmia Lake and the upper Tigris River drainages in Iran, is distinguished from its closest congeners (R. amarus and R. colchicus) by having short post-dorsal distance and caudal peduncle length and long head length. It is also characterized by one fixed diagnostic nucleotide substitutions and a K2P nearest neighbor distance of 1% to R. amarus and R. colchicus in the mtDNA COI barcode region.